Research Progress of Traditional Chinese and Western Medicine in the Treatment of Irritable Bowel Syndrome Based on 5-hydroxytryptamine - Pengning WU, Shuai XIONG, Xiaohan JIANG, Yi ZHANG, Chao LIANG, Min CHEN (Zhongguo quanke yixue, 2022)
Irritable bowel syndrome (IBS) is a gastrointestinal disorder with no structural damage and biochemical abnormality, and its pathogenic mechanism is still unclear. Variety of drugs, psychotherapy, diet regulation and other methods have been used by modern medicine to relieve symptoms, but the effect is not satisfactory. In recent years, TCM treatment of IBS has attracted widespread attention, especially for constipation type and diarrhea type. Among the many experiments, most of the traditional Chinese medicine experiments aimed at the 5-HT signaling pathway have achieved good results. Therefore, this paper summarizes the main mechanisms and results of traditional Chinese medicine based on 5-HT in the treatment of IBS, in order to provide a reference for subsequent research.